Novel system for the automatization of photogrammetric data capture for metrological tasks: application to study of gears. Issue 1 (October 2021) - Rodríguez, M; Rodríguez, P
Abstract: This paper presents a novel methodology for the macro-photogrammetric reconstruction of gears for metrological and maintenance purposes. The process presented includes the automation of close-range photogrammetric data acquisition using a referenced platform supported by measures gathered using an Articulated Coordinate Measure Machine and the subsequent Structure for Motion processing that allows the generation of dense 3D point cloud models with metrical scale and photorealistic colour texture of the gears. On these models, it is possible to directly take measurements, extract different profiles that can be exported in 2D formats and apply advanced processes that allow the computation of roughness and curvature parameters to evaluate the wear and possible defects or pathologies.